Development of a cryptographic protection system for information transmitted over open communication channels - V. F. Antonov (Современная наука и инновации, 2025)
Introduction. The object of the study in this paper is the information security system. The purpose of this study is to develop a system of cryptographic protection of service information transmitted over open communication channels using the TCP/IP protocol between the TCP server and the client in the concept of an information security system. The paper provides examples of various algorithms for cryptographic protection of information when transmitting information over open communication channels. Materials and methods. This article discusses special encryption algorithms: DES, Triple DES, Rijndael, RC2 and RSA. The selection of the desired algorithm in a specific work session is carried out by selecting from the drop-down list. After specifying the type of algorithm, you should select the key length in the next drop-down list. The presence of several encryption algorithms and the presence of different key lengths will significantly improve the cryptographic strength of the system being developed, since when a sent message is intercepted, the algorithm and key length can be arbitrary, which will make it difficult for unauthorized decryption of messages. Results and discussions. World experience shows that success in the field of information security largely depends on the degree of use of the latest technologies that implement the majority of open cryptographic algorithms used. A huge number of organizations spend large amounts of money to ensure the security of information transmitted both outside and within the organization. Moreover, in the second case, as a rule, less attention is paid. But this is a pressing problem today and to solve it you need a software product. Of course, information security problems cannot be solved only by developing software products, because the human factor remains the weak point of any system. Conclusion. The solutions that are proposed based on the results of the work performed within the framework of this article will enable users to transmit and receive information through open communication channels, both within the organization and outside, thereby ensuring the protection of information from unauthorized access and modification.